In-Depth Proteomic Characterization of Classical and Non-Classical Monocyte Subsets - Víctor Segura; M. Luz Valero; Laura Cantero; Javier Muñoz; Eduardo Zarzuela; Fernando García; Kerman Aloria; Javier Beaskoetxea; Jesús M. Arizmendi; Rosana Navajas; Alberto Paradela; Paula Díez; et al. (Proteomes, 2018)
Monocytes are bone marrow-derived leukocytes that are part of the innate immune system. Monocytes are divided into three subsets: classical, intermediate and non-classical, which can be differentiated by their expression of some surface antigens, mainly CD14 and CD16. These cells are key players in the inflammation process underlying the mechanism of many diseases. Thus, the molecular characterization of these cells may provide very useful information for understanding their biology in health and disease. We performed a multicentric proteomic study with pure classical and non-classical populations derived from 12 healthy donors. The robust workflow used provided reproducible results among the five participating laboratories. Over 5000 proteins were identified, and about half of them were quantified using a spectral counting approach. The results represent the protein abundance catalogue of pure classical and enriched non-classical blood peripheral monocytes, and could serve as a reference dataset of the healthy population. The functional analysis of the differences between cell subsets supports the consensus roles assigned to human monocytes.